Scenario Management and Requirements Tool (SMaRT) - Nordin, Azlin; Omar, Amirul Ikhwan; Megat Mohamed Amin, Megat Usaamah (2014)

(untitled)
The aim of this project is to develop a Scenario Management and Requirements Tool (SMaRT) to assist users involved in managing the Requirements Engineering (RE) process. The existing RE tools did not support or had less focus on scenario-based methodology, or missing some important RE features. SMaRT improves existing RE tool features to further support scenario-based RE methodology and to cover relevant RE processes i.e. analysis and negotiation, documentation, validation, and management. * Kotonya, G. , & Sommervile, I. (2003). Requirements engineering: Processes and techniques. John Wiley.